Synesthesia improves sensory memory, when perceptual awareness is high. (December 2018) - Rothen, Nicolas; Seth, Anil K.; Ward, Jamie
Abstract: Empirical evidence suggests that synesthesia is associated with enhanced sensory processing. A separate body of empirical literature suggests that synesthesia is linked to a specific profile of enhanced episodic and working memory performance. However, whether sensory (iconic) memory performance is also affected by synesthesia remains unknown. Therefore, we tested 22 grapheme-color synesthetes and compared their performance in a partial-report paradigm with 22 individually matched non-synesthete controls. Participants were briefly presented with a circular-letter array and required to report the identity of the letter at a probed target location after various delays. Furthermore, they were required to indicate the subjective clarity of the target letter after every trial. The results suggest that sensory memory performance is enhanced in synesthesia, but only when subjective clarity of the target letter is high. Additional exploratory analyses revealed that synesthetic consistency, which is widely used to confirm the genuineness of synesthesia, correlated significantly with performance in the partial report paradigm. We conclude that synesthesia does not generally enhance sensory memory performance, but that synesthetic experiences may enhance sensory memory performance when perceptual awareness of the target is high. Furthermore, the stability of synesthetic associations may be linked to sensory memory performance.